Architectural Support for Task Migration Concerning MPSoC - Aguiar, Alexandra; J. Filho, Sérgio; Santos, Tatiana G. dos; Marcon, César; Hessel, Fabiano (Anais do Workshop de Sistemas Operacionais (WSO); 2008: Anais do V Workshop de Sistemas Operacionais, 2008)
Embedded computing systems are currently present in a wide range of consumer goods and their main characteristic is the implicit specialized behavior but keeping a certain level of flexibility once it avoids redesigning due to small requirement changes. Thus, microprocessors usually are a good alternative to achieve such flexibility. Consequently, embedded systems designs make use of homogeneous or heterogeneous processors families for its complete implementation, which is known as Multiprocessor System-on-Chip (MPSoC), which can have a performance speed up through using dynamic load balancing strategies, such as task migration, to fairly distribute the existing tasks among all embedded processors. The objectives of this work are to discuss architectural aspects for embedded systems, which allow a dynamic task migration and its implications, as well as to present different techniques for the dynamic task migration showing their possible use in MPSoCs.